Asas-Asas Umum Pemerintahan yang Baik Sebagai Dasar Pejabat Pemerintah Untuk Melakukan Diskresi - Aprilian Nurahsan Ismail; Taufiqurrohman Syahuri (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study examines the concept of Freies Ermessen in government policy and how the principles of General Principles of Good Governance (GPGG) are used to establish the basis for discretionary actions. Freies Ermessen grants government officials the freedom to act without being entirely bound by law, primarily aiming to enhance public welfare. However, within the framework of a legal state, the use of discretion must meet GPGG elements such as public service objectives, active state administration actions, law-permitted actions, self-initiative, addressing urgent issues, and moral and legal accountability. This research employs normative legal methods to examine the internal aspects of positive law, focusing on how GPGG can be used as a concrete basis for public officials in exercising discretion. GPGG serves as a guideline for the government to ensure their actions align with legal purposes and avoid abuse of power. These principles also assist citizens in seeking justice and provide a basis for judges in reviewing administrative decisions. The study highlights the significance of shifting GPGG from unwritten to written law, as stipulated in Law Number 30 of 2014 on Government Administration, to facilitate officials in using these principles as guidelines. The implementation of discretion regulated by this law aims to streamline government administration, fill legal gaps, provide legal certainty, and overcome government stagnation for public benefit and interest.